Implementasi Model Pembelajaran Make a Match untuk Meningkatkan Motivasi dan Hasil Belajar Matematika Unsur-unsur Bangun Datar - Musdzalifah, Musdzalifah; Pratiwi, Ika Ari; Sofiyati, Dewi (Lembaga Yasin AlSys, 2025)
This study is motivated by the low level of student engagement in learning the topic of plane figure elements, which affects their motivation, interest in mathematics, and participation in group activities. The purpose of this research is to improve student motivation and learning outcomes through the implementation of the Make a Match learning model in mathematics instruction. The study used a classroom action research method conducted in two cycles, with stages including planning, action implementation, observation, and reflection. Data were collected through tests, observation, and documentation, and analyzed descriptively and comparatively. The research subjects were 12 third-grade students at SD 3 Barongan Kudus. The results show an improvement in learning outcomes, with the percentage of students meeting the Minimum Mastery Learning Criteria (KKTP) increasing from 75.00% in the first cycle to 83.33% in the second cycle. Additionally, student activity levels rose from 66.67% to 83.33%. The conclusion of this study is that the implementation of the Make a Match learning model significantly improves student motivation and learning outcomes in mathematics, particularly in the topic of plane figure elements. The implications of this research suggest that enjoyable and collaborative learning strategies can more effectively encourage student involvement in the learning process.